Acquisition, Maintenance and Relapse-Like Alcohol Drinking: Lessons from the UChB Rat Line - Israel, Yedy; Karahanian, Eduardo; Ezquer, Fernando; Morales, Paola; Ezquer, Marcelo; Rivera-Meza, Mario; Herrera-Marschitz, Mario; Quintanilla, María E. (Frontiers in Behavioral Neuroscience, 2017)
This review article addresses the biological factors that influence: (i) the acquisition of alcohol intake; (ii) the maintenance of chronic alcohol intake; and (iii) alcohol relapse-like drinking behavior in animals bred for their high-ethanol intake. Data from several rat strains/lines strongly suggest that catalase-mediated brain oxidation of ethanol into acetaldehyde is an absolute requirement (up 80%–95%) for rats to display ethanol’s reinforcing effects and to initiate chronic ethanol intake. Acetaldehyde binds non-enzymatically to dopamine forming salsolinol, a compound that is self-administered. In UChB rats, salsolinol: (a) generates marked sensitization to the motivational effects of ethanol; and (b) strongly promotes binge-like drinking. The specificity of salsolinol actions is shown by the finding that only the R-salsolinol enantiomer but not S-salsolinol accounted for the latter effects. Inhibition of brain acetaldehyde synthesis does not influence the maintenance of chronic ethanol intake. However, a prolonged ethanol withdrawal partly returns the requirement for acetaldehyde synthesis/levels both on chronic ethanol intake and on alcohol relapse-like drinking. Chronic ethanol intake, involving the action of lipopolysaccharide diffusing from the gut, and likely oxygen radical generated upon catechol/salsolinol oxidation, leads to oxidative stress and neuro-inflammation, known to potentiate each other. Data show that the administration of N-acetyl cysteine (NAC) a strong antioxidant inhibits chronic ethanol maintenance by 60%–70%, without inhibiting its initial intake. Intra-cerebroventricular administration of mesenchymal stem cells (MSCs), known to release anti-inflammatory cytokines, to elevate superoxide dismutase levels and to reverse ethanol-induced hippocampal injury and cognitive deficits, also inhibited chronic ethanol maintenance; further, relapse-like ethanol drinking was inhibited up to 85% for 40 days following intracerebral stem cell administration. Thus: (i) ethanol must be metabolized intracerebrally into acetaldehyde, and further into salsolinol, which appear responsible for promoting the acquisition of the early reinforcing effects of ethanol; (ii) acetaldehyde is not responsible for the maintenance of chronic ethanol intake, while other mechanisms are indicated; (iii) the systemic administration of NAC, a strong antioxidant markedly inhibits the maintenance of chronic ethanol intake; and (iv) the intra-cerebroventricular administration of anti-inflammatory and antioxidant MSCs inhibit both the maintenance of chronic ethanol intake and relapse-like drinking.